Grid configuration and land use : a syntactic study of Porto Alegre (Brasil) - Aguiar, Douglas Vieira de (1991)
This thesis is about the configuration of the urban grid. Configuration is understood here as a particular manner of arrangement which differentiates the layout of the street grid from one part of the town to another. The problem of how to describe, in objective terrns, the diversity of grid configurations that compose naturally evolved urban areas is a central concern in this investigation. This thesis is also about the scrutiny of relationships between grid configuration and the distribution of land use. It is conjectured in this respect that configurational factors given by the spatiol nature of the grid may affect the way in which land use is distributed in urban areas. A sample of urban areas - grid configurations and corresponding land use distributions- taken from the city of Porto Alegre (Brazil) is the object to be investigated. The simultaneity and interaction of markedly distinct grid configurations within the same city make of Porto Alegre a case where this research has fertile grounds for development. The investigation is centred on the study of the laws of the object. The urban grid will be assessed in terms of its internal laws and properties which, in a sub sequent step, will be statistically compared with the socio- economic dimension of the urban phenomenon given by the distribution of land use.